Lithium ion battery electrolyte and lithium ion battery
By using group-modified cyclotriphosphazene compounds as additives in the lithium-ion battery electrolyte, the electrode interface performance is improved and the stable SEI film is formed, which solves the problem of deterioration in the performance of lithium-ion batteries in the low-temperature environment, and improves the flame retardant performance of the electrolyte at high temperatures, achieving the full temperature range of battery performance.
Patent Information
- Application Number
- CN202411954302.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
The performance of lithium-ion batteries deteriorates in low-temperature environments, resulting in rapid attenuation of battery capacity, shortening of cycle life, and posing safety hazards. The existing electrolyte decomposes in high-temperature environments and damages the SEI membrane, resulting in a degradation of battery performance.
The cyclotriphosphazene compound with specific group modification is used as the first additive to improve the interface performance of the electrode surface, form a stable CEI film, and decompose it into phosphorus radicals at high temperature to eliminate hydrogen radicals, improving the flame retardant performance of the electrolyte; at low temperature, the negative electrode surface is covered by electrochemical polymerization products and redox products to form a compact and uniform SEI film to inhibit the decomposition of the electrolyte and protect the electrode material.
While maintaining the normal temperature and high temperature performance of lithium-ion batteries, it significantly improves the low temperature performance of the battery, extends the battery's cycle life, reduces safety risks, and broadens the working environment temperature range of the electrolyte.
Smart Images

Figure BDA0005215523810000031 
Figure BDA0005215523810000041 
Figure BDA0005215523810000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery electrolyte and a lithium ion battery. Background Art
[0002] Green renewable energy has replaced fossil fuels as the main trend, and the storage and conversion of green energy is of great significance to solving global warming. Lithium-ion batteries have the advantages of high operating voltage, high energy density, long cycle life, light weight and environmental protection, and are widely used in 3C products, power batteries and energy storage devices. In recent years, the temperature-sensitive field of lithium-ion batteries has received more and more attention. The applicable temperature of lithium-ion batteries is 0-40℃. When the temperature is lower than -20℃, the ion transmission of the battery interface is blocked at low temperature, and the interface impedance and interface polarization cause the battery capacity to decay rapidly, the internal structure is damaged, the cycle life is shortened, and the battery electrode reaction rate decreases, the ion mobility is low, and charging is difficult. Even when charging, lithium dendrites will be generated at the negative electrode, which is easy to cause safety problems such as short circuit. The deterioration of the performance of lithium-ion batteries at low temperatures limits their wide application in cold areas and extreme fields. At the same time, some electrolytes are optimized for low temperature environments, but the electrolytes sacrifice the high temperature performance of the battery, that is, the electrolyte decomposes and the SEI film is damaged in high temperature environments, resulting in a decrease in battery capacity and reduced cycle performance. Therefore, the demand for developing low-temperature lithium-ion batteries that are suitable for high and low temperatures is increasing.
[0003] Therefore, how to maintain the room temperature and high temperature performance of lithium-ion batteries while improving their low temperature performance is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a lithium ion battery electrolyte and a lithium ion battery. The electrolyte provided by the present invention broadens the working environment temperature range of the electrolyte, changes the solvation state of the lithium salt, and improves the low temperature performance of the lithium ion battery while maintaining the normal high temperature performance of the lithium ion battery.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a lithium ion battery electrolyte, wherein the lithium ion battery electrolyte comprises a first additive, a lithium salt and an organic solvent;
[0007] The first additive includes a cyclotriphosphazene compound modified with a fluorine-containing functional group and / or a cyclotriphosphazene compound modified with a fluorine-containing functional group and a nitrogen-containing functional group.
[0008] In the electrolyte provided by the present invention, a cyclotriphosphazene compound modified with a specific group is selected as the first additive, which has a lower HOMO (highest occupied molecular orbital) and a higher LUMO (lowest unoccupied molecular orbital), can be oxidized and reduced to form a stable CEI interface film on the electrode surface, improve the interface performance of the positive electrode, and decompose into phosphorus free radicals at high temperature, positively remove hydrogen free radicals in the gas phase, and improve the flame retardant performance of the electrolyte; at the same time, under low temperature conditions, during the charge and discharge process of the battery, the electrochemical polymerization product and the oxidation-reduction product are jointly covered on the surface of the negative electrode to form a more compact and uniform SEI film, which can inhibit the continuous decomposition of the electrolyte and protect the electrode material from corrosion, thereby improving the cycle performance of the battery, which is beneficial to Li + The migration of LiF in the SEI membrane reduces the impedance of the SEI membrane and improves the low-temperature performance of the battery. In addition, the fluorine in the fluorine-containing functional group and the phosphorus in the cyclotriphosphazene also have a synergistic effect of high-temperature flame retardancy, which can further optimize the structure of the CEI membrane, help form an inorganic interface membrane containing LiF, help improve the ion conductivity rate, and promote Li + The diffusion of lithium ion batteries is improved, the high-temperature cycle stability is improved, thereby broadening the working environment temperature range of the electrolyte, changing the solvation state of the lithium salt, and improving the low-temperature performance of lithium ion batteries while maintaining the room-temperature and high-temperature performance of lithium ion batteries.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] Preferably, the first additive comprises a cyclotriphosphazene compound modified with a fluorine-containing functional group and a nitrogen-containing functional group.
[0011] The present invention preferably uses a cyclotriphosphazene compound modified with both a fluorine-containing functional group and a nitrogen-containing functional group as the first additive. On the one hand, under a high temperature environment, when the fluorine-containing functional group is modified, the cyclotriphosphazene ring can be ring-opened and polymerized, preferentially forming an interface film rich in inorganic components on the electrode surface, changing the interface properties, and can be decomposed into phosphorus free radicals at high temperature to remove hydrogen free radicals, forming a protective carbon layer at high temperature, and further improving the flame retardant properties and high-temperature interface stability of the electrolyte; on the other hand, under a low temperature environment, the nitrogen-containing functional group modification can preferentially form a more uniform, compact, low-impedance SEI film on the surface of the negative electrode, thereby having more excellent low-temperature performance, room-temperature performance and high-temperature performance, greatly broadening the temperature use range of the electrolyte.
[0012] Preferably, the first additive has a structural formula shown in Formula I:
[0013]
[0014] Among them, R 1 Any one selected from the group represented by the structure of formula II, the group represented by the structure of formula III, a C1-C8 alkyl group, a C2-C8 alkenyl group, an amino group, a C6-C20 aryl group, a cyano group, a C1-C8 alkylsilyl group, an ether group, a siloxy group, a carboxyl group, a C1-C8 sulfonyl group, a hydroxyl group or a halogen-containing group.
[0015] The first additive provided by the present invention has both -F group and isocyanate group, on the one hand, the synergistic coordination effect of fluorine and phosphorus under high temperature flame retardancy is exerted; on the other hand, the -NCO functional group in the isocyanate group has low LOMO and high HOMO, and the electrochemical polymerization product and the redox product are preferentially covered on the surface of the negative electrode to form a more compact and uniform SEI film, which can inhibit the continuous decomposition of the electrolyte and protect the electrode material from corrosion, thereby improving the cycle performance of the battery, which is beneficial to Li + The migration in the SEI film reduces the impedance of the SEI film and further improves the low-temperature performance of the battery.
[0016] When the first additive provided by the present invention has both a -F group and a five-membered aromatic heterocyclic group, on the one hand, the synergistic coordination effect of fluorine and phosphorus under high-temperature flame retardancy is exerted; on the other hand, the nitrogen-containing five-membered aromatic heterocyclic group has two electronegative heteroatoms (isoxazole) of nitrogen and oxygen, has a low LOMO and a high HOMO, and can preferentially form a more uniform, compact, low-impedance SEI film on the surface of the negative electrode. The constructed SEI film is rich in inorganic structure, which is helpful for Li + Migration in the SEI film better improves the low-temperature performance of the battery.
[0017] The formula II is:
[0018]
[0019] Among them, R 2 Any one selected from -H, C1-C4 straight chain or branched alkyl, C1-C4 straight chain or branched amino, C1-C4 straight chain or branched carbonyl, C1-C4 straight chain or branched ether, C1-C4 straight chain or branched ester or C1-C4 straight chain or branched sulfonyl.
[0020] Preferably, the formula III is:
[0021]
[0022] Among them, R 3R is selected from a single bond, a C1-C8 straight or branched alkylene group, -NH-, -O-, -CO-, -SO-, -COO-, -OCO-, -OS(O)O-, or a divalent group formed by replacing one or at least two -CH2- in the C1-C8 straight or branched alkylene group by any one of -NH-, -O-, -CO-, -SO-, -COO-, -OCO- or -OS(O)O-; 4 and R 5 Each is independently selected from any one of a C1-C5 alkyl group, a C2-C5 alkenyl group, a C2-C5 alkynyl group, an amino group, an ether group, a carboxyl group, a C1-C8 sulfonyl group, a halogen-containing group or a hydroxyl group.
[0023] Preferably, the group of the structure shown in formula II has any one of the structural formulas shown in formula II-1 to formula II-10:
[0024]
[0025] Preferably, the first additive has any one of the structural formulas shown in Formula I-1 to Formula I-10:
[0026]
[0027] Preferably, the group of the structure represented by formula III has any one of the structures represented by formulas III-1 to III-12:
[0028]
[0029] Preferably, the first additive has any one of the structural formulas shown in Formula I-11 to Formula I-22:
[0030]
[0031] It should be noted that the specific substance of the first additive in the present invention can be directly synthesized by conventional synthetic substitution methods in the prior art without special limitation, and those skilled in the art can make adaptive selection and adjustment according to actual needs.
[0032] Preferably, the mass of the first additive is 0.01% to 2% of the total mass of the electrolyte, for example 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8% or 2%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In the present invention, the mass of the first additive is regulated to be 0.01% to 2% of the total mass of the electrolyte, which is more conducive to the fluorine-containing functional group-modified and nitrogen-containing functional group-modified cyclotriphosphazene compounds to play the role of fluorine and phosphorus, and / or -NCO functional groups in the electrolyte. The functional groups can preferentially form a more uniform, compact, low-impedance SEI film on the surface of the negative electrode, and the constructed SEI film is rich in inorganic structure, thereby improving the Li + The migration rate in the SEI film better improves the low-temperature performance of the battery.
[0034] Preferably, the electrolyte further comprises a second additive.
[0035] Preferably, the second additive includes any one of fluoroethylene carbonate, vinylene carbonate, diethyl fluoromalonate, 1,3-dioxolane, tris(2,2,2-trifluoroethyl)phosphate, γ-butyrolactone, fluorobenzene, 1,3-propane sultone (PS), ethylene sulfate or vinyl ethylene carbonate, or a combination of at least two thereof.
[0036] The present invention adds a second additive to the electrolyte, which can be adaptively selected and adjusted according to specific needs, and the second additive is selected by conventional technology. The present invention is applicable to all types of conventional additives that can be known within a reasonable range by technicians in this field.
[0037] For example, it can be a film-forming additive (such as fluoroethylene carbonate (FEC) and vinylene carbonate (VC)). The additional addition of film-forming additives also helps the formation of the SEI film, and the SEI film is dense, stable and has low impedance, high density, low dielectric constant and low surface tension, thereby effectively reducing the low-temperature delithiation potential and reducing the SEI and CEI impedance; for example, it can be a low-impedance additive (such as 1,3-dioxolane (DOL), vinyl ethylene carbonate (VEC), γ-butyrolactone (GBL) and (2,2,2-trifluoroethyl) phosphate (TFP), 1,1,2,2-tetrafluoroethyl -2,2,3,3-tetrafluoropropyl ether (TTE), fluorobenzene (FB)), low-impedance additives have the advantages of low melting point and high boiling point, can be used as diluents for electrolytes, contribute to weak solvation structure, improve desolvation performance, promote the formation of low-impedance film on the negative electrode surface, reduce battery polarization, increase film conductivity, improve Li+ ion migration in low temperature environments, and improve conductivity; for example, they can also be high-temperature additives (such as 1,3-propane sultone (PS), ethylene sulfate (DTD) and vinyl ethylene carbonate (VEC)), which can significantly improve the high-temperature characteristics of the battery cell.
[0038] Preferably, the mass of the second additive is 1% to 6% of the total mass of the electrolyte, for example 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In the present invention, the mass of the second additive is controlled to be 1% to 6% of the total mass of the electrolyte, so that the second additive can better play its corresponding role according to the specific substance type, and cooperate with other components in the electrolyte to better improve the performance of the electrolyte.
[0040] Preferably, the lithium salt includes a main component lithium salt, and the main component lithium salt includes any one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethanesulfonyl)imide, or a combination of at least two of them, preferably at least two of them.
[0041] The main component lithium salt provided by the present invention, in addition to the types of lithium salts mentioned above, also includes other conventional types of lithium salts that can be used as electrolytes. The present invention is applicable to all conventional lithium salts for electrolytes that can be known within a reasonable range by those skilled in the art.
[0042] Furthermore, the present invention selects the above-defined lithium salt types to better cooperate with other components in the electrolyte to play a role.
[0043] Lithium hexafluorophosphate (LiPF 6 ) has high electrochemical stability and conductivity, and is easily soluble in organic solvents. It can form a LiF-rich SEI film at the negative electrode interface, but has poor thermal stability. When the temperature is higher than 60°C, the decomposition product is easily hydrolyzed to produce HF, which destroys the structure and performance of the battery. Under low temperature conditions, as the solvent reacts with LiPF 6 The solubility of lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) has good solubility and high oxidation potential, strong dissociation ability for Li+, thermal decomposition temperature above 360℃, and resistance to hydrolysis, but when the voltage is higher than 3.7V, TFSI- will strongly corrode the Al current collector; lithium bis(fluorosulfonyl imide) (LiFSI) has high dissociation ability, which is conducive to the formation of SEI. At the same time, it can also effectively improve the characteristics of low-temperature discharge and inhibit the flatulence of soft-pack batteries, but when the voltage is higher than 4.2V, FSI- will strongly corrode the Al current collector. Therefore, there are many problems with the stability of the electrolyte by a single lithium salt, and a combination of lithium salts is needed to complement each other and improve the stability of the electrolyte by lithium salts. Therefore, different types of lithium salts can be used to better play their role.
[0044] Preferably, the mass ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is 1:(0.5-0.8), such as 1:0.5, 1:0.6, 1:0.7 or 1:0.8, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the mass ratio of lithium hexafluorophosphate to lithium bis(trifluoromethanesulfonyl)imide is 1:(0.5-0.8), such as 1:0.5, 1:0.6, 1:0.7 or 1:0.8, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the mass ratio of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide is 1:(0.3-1):(0.3-1), for example, 1:0.3:0.3, 1:0.3:0.5, 1:0.3:0.8, 1:0.5:0.3, 1:0.5:0.5, 1:0.5:0.8, 1:0.8:0.3, 1:0.8:0.5, 1:0.8:0.5, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0047] Preferably, the mass of the main component lithium salt is 10% to 20% of the total mass of the electrolyte, for example 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the lithium salt further includes a lithium salt additive, and the lithium salt additive includes any one of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate or lithium tetrafluoroborate, or a combination of at least two thereof.
[0049] In the present invention, on the basis of the main component salt, a lithium salt additive is added, which can further reduce the internal resistance of the SEI film and improve the lithium ion conduction, and has a good effect on both high and low temperatures.
[0050] Lithium difluorophosphate (LiPO 2 F 2 ) as an intermediate product can reduce the internal resistance of the SEI film and improve the lithium ion conduction, and has a good effect on both high and low temperatures. Lithium bis(oxalatoborate) (LiBOB) has good overcharge resistance, hygroscopicity and film-forming properties, and can form a stable SEI film on the negative electrode surface, but the film impedance is large, it is sensitive to water, and is not easily soluble in carbonate solvents; lithium tetrafluoroborate (LiBF 4) has a wider operating temperature range, better thermal stability, and better low-temperature performance, but has low conductivity and poor film-forming properties. Lithium difluorooxalatoborate (LiDFOB) combines LiBOB and LiBF 4 It has the advantages of being able to form a stable SEI film on the surface of the negative electrode. It also has the advantages of good film-forming properties and low-temperature properties. It has the function of inhibiting electrolyte oxidation and passivating aluminum foil, and shows significantly excellent low-temperature discharge performance. Therefore, the selection of suitable lithium salt additives can better improve the performance of the electrolyte.
[0051] Preferably, the mass of the lithium salt additive is 0.3% to 0.8% of the total mass of the electrolyte, for example 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Furthermore, among the lithium salt additives provided by the present invention, a combination of lithium difluorooxalatoborate (LiDFOB) and lithium dioxalatoborate (LiBOB) or a combination of lithium difluorooxalatoborate (LiDFOB) and lithium tetrafluoroborate (LiBF 4 ) combination. And lithium difluorooxalatoborate (LiDFOB): lithium dioxalatoborate (LiBOB) / lithium tetrafluoroborate (LiBF 4 ) can be 1:(0.1-1), for example 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, the organic solvent comprises a carbonate organic solvent and / or a carboxylate organic solvent.
[0054] Preferably, the carbonate organic solvent includes a cyclic carbonate organic solvent and / or a linear carbonate organic solvent.
[0055] Preferably, the organic solvent further comprises a diluent, and the diluent comprises ethylene glycol diacetate and / or tetrahydrofuran.
[0056] It should be noted that the specific material types of the organic solvents provided in the present invention are all conventional technical solutions; the present invention is applicable to the material types of organic solvents that can be known to technical personnel in this field within a reasonable range, and the present invention can adaptively select and adjust the organic solvent of the electrolyte according to actual needs, for example, it can be a ternary, quaternary or more solvent system.
[0057] For example, the melting point of the electrolyte can be lowered by adding a low-melting-point carboxylic acid ester solvent, further improving the low-temperature performance of the electrolyte; diluents can also be added to improve the low-temperature performance, such as ethylene glycol diacetate (EGD) has a low freezing point, low viscosity, and low binding energy with lithium ions, which is beneficial to the lithium ion deintercalation process at low temperatures; tetrahydrofuran (THF) has a lower viscosity, a lower melting point, and a higher solubility in LiTFSI, and has higher conductivity and lower viscosity at low temperatures, which is beneficial to the diffusion of lithium ions in a low-temperature environment.
[0058] For example, the cyclic carbonate organic solvent includes but is not limited to ethylene carbonate (EC) and / or propylene carbonate (PC); the linear carbonate organic solvent includes but is not limited to at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC); the carboxylate organic solvent includes but is not limited to at least one of ethyl acetate (EA), methyl acetate (MA, propyl acetate (PA), ethyl propionate (EP) and methyl butyrate (MB).
[0059] More preferably, the mass ratio of the cyclic carbonate organic solvent, the carboxylate organic solvent, and the linear carbonate organic solvent / diluent is (0.8-1.5):(1-2):(0.5-1.2), for example, 0.8:1:0.5, 0.8:1.5:0.5, 0.8:2:0.5, 1:1:0.5, 1:1.5:0.5, 1:2:0.5, 1.5:1:0.5, 1.5: :1.5:0.5, 1.5:2:0.5, 0.8:1:0.5, 0.8:1:0.5, 0.8:1:0.5, 0.8:2:0.5, 0.8:2:0.5, 0.8:2:0.5, 0.8:1:0.8, 0.8:1.5:0.8, 0.8:2:0.8, 0.8:1:1.2, 0.8:1.5:1.25 or 0.8:2:1.2, etc.
[0060] Preferably, the mass of the organic solvent is 65% to 85% of the total mass of the electrolyte, for example 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83% or 85%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] Secondly, the present invention does not impose any special limitation on the specific preparation method of lithium-ion battery electrolyte. Except for the limitation on the electrolyte components mentioned above, the remaining preparation conditions are all conventional technical methods. The present invention is applicable to any conventional electrolyte preparation method that can be known to technical personnel in this field within a reasonable range.
[0062] Exemplarily, the present invention provides a method for preparing an electrolyte:
[0063] S1: weigh a certain amount of organic solvent, lithium salt and additive according to the formula; S2: in an argon atmosphere glove box with a moisture content of ≤1ppm, mix the solvent in a certain mass ratio, add a molecular sieve dehydrating agent, and let it stand; S3: then dissolve the dry lithium salt in the solvent, stir until the solution is completely uniform and the liquid appears clear and transparent; S4: then add the additive to the above liquid, mix well and pour into a filtering device to remove impurities, thereby obtaining an impurity-free lithium-ion battery electrolyte.
[0064] Among them, the specific raw materials and formula quantities in the above preparation process can be adaptively matched according to the technical solution provided in the first aspect.
[0065] In a third aspect, the present invention further provides a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery electrolyte as described in the first aspect.
[0066] Compared with the prior art, the present invention has the following beneficial effects:
[0067] In the electrolyte provided by the present invention, a cyclotriphosphazene compound modified with a specific group is selected as the first additive, which has a lower HOMO (highest occupied molecular orbital) and a higher LUMO (lowest unoccupied molecular orbital), can be oxidized and reduced to form a stable CEI interface film on the electrode surface, improve the interface performance of the positive electrode, and decompose into phosphorus free radicals at high temperature, positively remove hydrogen free radicals in the gas phase, and improve the flame retardant performance of the electrolyte; at the same time, under low temperature conditions, during the charge and discharge process of the battery, the electrochemical polymerization product and the oxidation-reduction product are jointly covered on the surface of the negative electrode to form a more compact and uniform SEI film, and at the same time, the continuous decomposition of the electrolyte can be suppressed and the electrode material can be protected from corrosion, thereby improving the cycle performance of the battery, facilitating the migration of Li+ in the SEI film, thereby reducing the impedance of the SEI film and improving the low-temperature performance of the battery; in addition, the fluorine in the fluorine-containing functional group and the phosphorus in the cyclotriphosphazene also have a synergistic effect of high-temperature flame retardant performance, which can further optimize the structure of the CEI film, help to form an inorganic interface film containing LiF, help to improve the ion conductivity rate, and promote Li + The diffusion of lithium ion batteries is improved, the high-temperature cycle stability is improved, thereby broadening the working environment temperature range of the electrolyte, changing the solvation state of the lithium salt, and improving the low-temperature performance of lithium ion batteries while maintaining the room-temperature and high-temperature performance of lithium ion batteries. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0069] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0070] In the description of this application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0071] Exemplarily, the present invention provides a nucleophilic substitution synthesis method for a first additive, the nucleophilic substitution synthesis method comprising:
[0072] (1) For Ⅰ 1 Types of synthesis methods:
[0073]
[0074] A. Preparation of Sodium Alcohol Salt:
[0075] First, THF was dehydrated with calcium hydride, dried and filtered, and then the formula II was added in a ratio of 1:1 1 Alcohols or formula III 1 Add alcohol and metallic sodium or sodium hydride (sodium hydride should be washed twice with tetrahydrofuran to remove the protective substance on the surface of sodium hydride for subsequent reaction) to the THF solution. 1 Alcohols or formula III 1 The alcohol was slowly added to the flask containing metallic sodium through a constant pressure dropping funnel. After the addition was completed and the reaction was continued for 2 hours, the ice bath was removed. At the same time, in order to ensure the smooth progress of the reaction, the reaction temperature was controlled not to exceed 20°C, mechanical stirring was started, and the reaction was continued for 24 hours to finally obtain Formula II 1 Sodium alkoxide or formula III 1 Sodium alkoxide in THF;
[0076] B Nucleophilic substitution reaction:
[0077] The reaction is completed 1 Sodium alkoxide or formula III 1 Sodium alcoholate solution (Formula II 1 Sodium alkoxide or formula III 10.01~0.015mol of alcohol and 200~240mL of THF) are poured into a three-necked flask containing sodium salt of alcohol and mixed evenly. Then weigh 0.01mol of an appropriate amount of hexafluorocyclophosphazene and dissolve it in 60mL of tetrahydrofuran to obtain a hexafluorocyclophosphazene solution. In a nitrogen atmosphere and an ice bath, the cyclophosphazene solution is slowly added to the three-necked flask containing sodium salt through a constant pressure dropping funnel. After 2 hours of dropwise addition, the ice bath is removed, and the mixture is stirred overnight (≥12 hours) at room temperature (controlled at 20°C). Then, the three-necked flask is placed in an oil bath pot, stirred and heated to 84°C, and the product is obtained by reaction for 48 hours. After the reaction is completed, the THF is removed by heating and evaporation, and then washed three times with 200mL of deionized water. After the product is dissolved in deionized water, the solution is poured into a dialysis bag of the corresponding molecular weight for dialysis to wash away impurities. Then, the dialyzed product is vacuum dried at 60°C to obtain the final product.
[0078] (2) For Ⅰ 2 Types of synthesis methods:
[0079]
[0080] In 150mL acetonitrile, under nitrogen atmosphere and ice bath, 0.9mmol cyclophosphazene solution was slowly added to the three-necked flask through a constant pressure dropping funnel. After 2h of the addition, the ice bath was removed and ultrasonicated at room temperature 20℃ for 30min to completely dissolve the hexafluorocyclophosphazene. Then, under nitrogen atmosphere and ice bath, the -NH 2 Formula II 2 Or Formula III 2 Slowly add it dropwise into the three-necked flask through a constant pressure dropping funnel, and the hexafluorocyclophosphazene and formula II 3 Or Formula III 3 The molar ratio of addition is 1:1 to 1:1.5. 2 hours after the addition, 4 mL of triethylamine is slowly added dropwise into a three-necked flask. 2 hours after the addition, the ice bath is removed, and the reaction is carried out at 40°C for 4 hours under ultrasound. Then, 200 mL of deionized water is used for three washes. Then, 10 wt% KOH solution is used for alkaline washing and separation, and the upper layer of liquid is separated and dried with anhydrous magnesium sulfate to obtain the final product.
[0081] (3) For Ⅰ 3 Types of synthesis methods:
[0082]
[0083] Under acetonitrile conditions, in a nitrogen atmosphere and an ice bath, slowly add the cyclophosphazene solution to the three-necked flask through a constant pressure dropping funnel. Remove the ice bath 2 hours after the addition is complete, and perform ultrasound at room temperature 40°C for 30 minutes to completely dissolve the hexafluorocyclophosphazene. Then, in a nitrogen atmosphere and an ice bath, add the compound of formula II with -OH or -COOH 3Or Formula III 3 Slowly add it dropwise to the three-necked flask through a constant pressure dropping funnel. Remove the ice bath 2 hours after the addition is completed. 3 Or Formula III 3 The molar ratio of the added is 1:1 to 1:1.5, and the reaction is carried out at 20°C for 1 hour under ultrasonic conditions; then, 200 mL of deionized water is used for three washes, and then a 10 wt% KOH solution is used for alkaline washing and separation, and the upper layer of liquid is separated and dried with anhydrous magnesium sulfate to obtain the final product.
[0084] In addition, the molecular structure of the first additive synthesized by the present invention is confirmed by infrared spectroscopy.
[0085] Formula I 1 Type products at 1255~1270cm -1 The PN characteristic peak in the hexafluorocyclophosphazene structure appears at 930-940cm -1 The characteristic peak of hexafluorocyclophosphazene PF at 1060-1070 cm -1 PO characteristic peak appears; for modified functional group II 1 Type, present at 2240~2255cm -1 The characteristic peak of -NCO group; for the modified functional group III 1 Type, present at 1590~1660cm -1 The characteristic peak of -CN in the isoxazole ring is at 1455-1460 cm -1 The characteristic peak of -C=C in the isoxazole ring is at 1155-1160 cm -1 The characteristic peak of -CO in the isoxazole ring is at 3125-3130 cm -1 、3030~3040cm -1 The characteristic -CH peak in the isoxazole ring.
[0086] Example 1
[0087] This embodiment provides a lithium-ion battery electrolyte, which includes an organic solvent, a first additive, a second additive, a main component salt, and a lithium salt additive.
[0088] The specific components in the electrolyte of this embodiment and the mass proportions of the components (expressed in mass percentage) are shown in Table 1.
[0089] Example 2-16
[0090] The differences between Example 2-16 and Example 1 are shown in Table 1.
[0091] Embodiment 17
[0092] The difference between this embodiment and embodiment 1 is that the first additive in this embodiment has a structural formula shown in formula I-23:
[0093]
[0094] The components and contents of the remaining electrolytes are consistent with those in Example 1.
[0095] Table 1
[0096]
[0097]
[0098]
[0099]
[0100] Examples 18-20
[0101] The differences between Examples 18-20 and Example 1 are shown in Table 2.
[0102] Table 2
[0103]
[0104]
[0105] Comparative Examples 1-3
[0106] The differences between Comparative Examples 1-3 and Example 1 are shown in Table 3.
[0107] Table 3
[0108]
[0109]
[0110] The electrolytes provided in Examples 1-20 and Comparative Examples 1-3 were applied to lithium-ion batteries and performance tests were performed.
[0111] (1) Battery preparation:
[0112] a) Preparation of positive electrode: The positive electrode active material lithium iron phosphate, conductive agent conductive carbon black, and binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) solution at a weight ratio of 96.7:1.4:1.9 to form positive electrode slurry. A 12μm carbon-coated aluminum foil is used as the positive electrode current collector. The positive electrode slurry is coated on the aluminum foil, and the positive electrode sheet is made after baking, rolling, die cutting, and slitting. The compacted density of the positive electrode is 2.40g / cm 3 .
[0113] b) Preparation of negative electrode: artificial graphite, conductive agent (SP), binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 95.5:1:1.8:1.7 to form negative electrode slurry. A 6μm thick copper foil is used as the negative electrode current collector. The negative electrode slurry is coated on the copper foil, and the negative electrode sheet is made after baking, rolling, die cutting, and slitting. The compacted density of the negative electrode is 1.55g / cm 3 .
[0114] c) Diaphragm: Use 9+3μm thickness, ceramic+PE single-sided coated diaphragm.
[0115] d) Electrolyte: The electrolytes provided in Examples 1-20 and Comparative Examples 1-3 are respectively selected.
[0116] e) Preparation of lithium-ion batteries: The prepared positive electrode sheets, separators, and negative electrode sheets are stacked in the order of positive electrode-separator-negative electrode-separator to obtain bare cells, and then the bare cells are assembled and packaged, injected with electrolytes of the embodiments and comparative examples, formed, and subjected to capacity separation tests, etc., to finally prepare lithium-ion batteries.
[0117] (2) Performance test:
[0118] Cyclic performance tests were conducted at -45℃ / -20℃ / 25℃ / 45℃ respectively: Under different temperature conditions, the lithium-ion battery was charged to 3.65V at 1C constant current, charged to 0.05C at 3.65V, left for 10 minutes, and discharged to 2.5V at 1C constant current. The above is one charge and discharge cycle. After formation and capacity separation, the obtained battery was subjected to 100 charge and discharge cycles under corresponding temperature conditions.
[0119] The discharge capacity at the third cycle is used as a benchmark, and the capacity retention rate is used as an indicator for evaluating the cycle performance of lithium-ion batteries; cycle capacity retention rate = discharge capacity at the 100th cycle / discharge capacity at the third cycle×100%.
[0120] The test results of the above tests are shown in Table 4.
[0121] Table 4
[0122]
[0123]
[0124] Combining Tables 1 to 4, we can get:
[0125] Compared with Example 17, Examples 1 to 16 add a trace amount of nitrogen-containing fluorine-functionally modified cyclotriphosphazene compounds shown in Formula 1. The fluorinated cyclotriphosphazene compounds are functionally modified with nitrogen-containing isocyanate groups or nitrogen-containing five-membered aromatic heterocyclic groups and used as wide-temperature range additives for electrolytes. On the one hand, under high temperature conditions, the fluorinated cyclophosphazene can undergo ring-opening polymerization to preferentially form an inorganic component-rich interface film on the electrode surface, thereby changing the interface properties, and can be decomposed into phosphorus radicals at high temperature to remove hydrogen radicals, thereby forming a protective carbon layer at high temperature, thereby further improving the flame retardant properties and high-temperature interface stability of the electrolyte. On the other hand, under low temperature conditions, the isocyanate groups or five-membered aromatic heterocyclic groups can preferentially form a more uniform, compact, low-impedance SEI film on the surface of the negative electrode, thereby effectively improving the charge and discharge performance at low temperature and the high-temperature cycle performance while maintaining good cycle performance at room temperature, thereby broadening the temperature service range of the electrolyte.
[0126] Compared with Comparative Example 1, Examples 1 and 3 to 5 show that LiPF 6 It does not have good low temperature performance at low temperatures. The use of mixed lithium salts can effectively improve the low temperature performance of the electrolyte. LiTFSI and LiFSI have high stability and high conductivity, which is similar to LiPF 6 The two are mixed and used together as the lithium salt component in the electrolyte, and the amount of LiPF6 added is greater than LiTFSI / LiFSI, which makes the electrolyte have stable Li+ ion migration conductivity in a wider temperature window, better charge and discharge performance and good cycle stability.
[0127] Compared with Comparative Example 2, LiODFB and LiBF 4 / LiBOB mixed use can just make up for each other's shortcomings and play a synergistic role, LiODFB+LiBF 4 Or LiODFB+LiBOB as lithium supplement additives, on the one hand, passivate the aluminum foil to inhibit positive electrode corrosion and prevent iron precipitation, on the other hand, it is beneficial to reduce the charge transfer resistance and increase the diffusion rate of lithium ions at the interface of electrode materials, thereby effectively improving the low-temperature performance of the electrolyte.
[0128] Compared with Examples 1 to 16 and Comparative Example 2 and Comparative Example 3, the use of low melting point solvents such as carboxylates, EGD, THF, etc. can further reduce the viscosity and freezing point of the electrolyte and improve the low temperature performance of the electrolyte. FEC and VC make the SEI film formed on the interface more stable under low temperature conditions and increase the conductivity of the electrolyte solution at low temperatures. DEFM, DOL, TFP, GBL, TTE, etc. have lower melting points and non-polar solvents, which reduce the viscosity of the electrolyte under low temperature conditions and make the SEI film formed on the interface more stable, thereby improving the conductivity of the electrolyte solution at low temperatures, but have an impact on high temperature performance. PS or VEC can enhance the flame retardant properties of the electrolyte and improve the high temperature performance of the electrolyte, thereby broadening the temperature service range of the electrolyte.
[0129] In Example 1, compared with Example 18, Example 19, and Example 20, the optimum addition amount of the cyclotriphosphazene compound modified with a specific group as the first additive is 0.01% to 2%, and further, the optimum addition amount is 0.4 to 0.6%. When the addition amount of the cyclotriphosphazene compound modified with a specific group is too small, the effect of improving the low temperature charge and discharge performance and high temperature cycle performance of the battery is not significantly played; when the addition amount of the cyclotriphosphazene compound modified with a specific group is too large, it is easy to promote the formation of a thicker SEI film, increase the internal resistance of the battery, reduce the battery ion transfer rate, and reduce the low temperature charge and discharge performance and high temperature cycle performance.
[0130] In summary, in the electrolyte provided by the present invention, a cyclotriphosphazene compound modified with a specific group is selected as the first additive, which has a lower HOMO (highest occupied molecular orbital) and a higher LUMO (lowest unoccupied molecular orbital), can be oxidized and reduced on the electrode surface to form a stable CEI interface film, improve the interface performance of the positive electrode, and decompose into phosphorus free radicals at high temperature, positively remove hydrogen free radicals in the gas phase, and improve the flame retardant performance of the electrolyte; at the same time, under low temperature conditions, during the charge and discharge process of the battery, the electrochemical polymerization product and the redox product are jointly covered on the surface of the negative electrode to form a more compact and uniform SEI film, and at the same time, the continuous decomposition of the electrolyte can be inhibited and the electrode material can be protected from corrosion, thereby improving the cycle performance of the battery, facilitating the migration of Li+ in the SEI film, thereby reducing the impedance of the SEI film and improving the low temperature performance of the battery; in addition, the fluorine in the fluorine-containing functional group and the phosphorus in the cyclotriphosphazene also have a synergistic effect of high temperature flame retardant performance, which can further optimize the structure of the CEI film, help to form an inorganic interface film containing LiF, help to improve the ion conductivity rate, and promote Li + The diffusion of lithium ion batteries is improved, the high-temperature cycle stability is improved, thereby broadening the working environment temperature range of the electrolyte, changing the solvation state of the lithium salt, and improving the low-temperature performance of lithium ion batteries while maintaining the room-temperature and high-temperature performance of lithium ion batteries.
[0131] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium ion battery electrolyte, characterized in that: The lithium ion electrolyte comprises a first additive, a lithium salt and an organic solvent; The first additive includes a cyclotriphosphazene compound modified with a fluorine-containing functional group and / or a cyclotriphosphazene compound modified with a fluorine-containing functional group and a nitrogen-containing functional group.
2. The lithium ion battery electrolyte according to claim 1, characterized in that: The first additive includes a cyclotriphosphazene compound modified with a fluorine-containing functional group and a nitrogen-containing functional group; Preferably, the first additive has a structural formula shown in Formula I: Wherein, R1 is selected from any one of a group of the structure shown in formula II, a group of the structure shown in formula III, a C1-C8 alkyl group, a C2-C8 alkenyl group, an amino group, a C6-C20 aryl group, a cyano group, a C1-C8 alkylsilyl group, an ether group, a siloxy group, a carboxyl group, a C1-C8 sulfonyl group, a hydroxyl group or a halogen-containing group; The formula II is: Wherein, R2 is selected from a single bond, a C1-C8 straight or branched alkylene, -NH-, -O-, -CO-, -SO-, -COO-, -OCO-, -OS(O)O-, or a divalent group formed by replacing one or at least two -CH2- in the C1-C8 straight or branched alkylene with any one of -NH-, -O-, -CO-, -SO-, -COO-, -OCO- or -OS(O)O-; The formula III is: Wherein, R3 is selected from a single bond, a C1-C8 straight or branched alkylene, -NH-, -O-, -CO-, -SO-, -COO-, -OCO-, -OS(O)O-, or a divalent group formed by replacing one or at least two -CH2- in the C1-C8 straight or branched alkylene by any one of -NH-, -O-, -CO-, -SO-, -COO-, -OCO- or -OS(O)O-; R4 and R5 are each independently selected from any one of a C1-C5 alkyl group, a C2-C5 alkenyl group, a C2-C5 alkynyl group, an amino group, an ether group, a carboxyl group, a C1-C8 sulfonyl group, a halogen-containing group or a hydroxyl group.
3. The lithium ion battery electrolyte according to claim 2, characterized in that: The group of the structure shown in Formula II has any one of the structures shown in Formula II-1 to Formula II-10:
4. The lithium ion battery electrolyte according to claim 3, characterized in that: The first additive has any one of the structural formulas shown in Formula I-1 to Formula I-10:
5. The lithium ion battery electrolyte according to claim 3, characterized in that: The group of the structure represented by formula III has any one of the structures represented by formulas III-1 to III-12:
6. The lithium ion battery electrolyte according to claim 5, characterized in that: The first additive has any one of the structural formulas shown in Formula I-11 to Formula I-22:
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The mass of the first additive is 0.01% to 2% of the total mass of the electrolyte.
8. The lithium ion battery electrolyte according to claim 1, characterized in that: The electrolyte further includes a second additive; Preferably, the second additive includes any one of fluoroethylene carbonate, vinylene carbonate, diethyl fluoromalonate, 1,3-dioxolane, tris(2,2,2-trifluoroethyl)phosphate, γ-butyrolactone, fluorobenzene, 1,3-propane sultone (PS), ethylene sulfate or vinyl ethylene carbonate, or a combination of at least two thereof; Preferably, the mass of the second additive is 1% to 6% of the total mass of the electrolyte.
9. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt includes a main component lithium salt, and the main component lithium salt includes any one or a combination of at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethanesulfonyl)imide, preferably at least two of them; Preferably, the mass ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is 1:(0.5-0.8); Preferably, the mass ratio of lithium hexafluorophosphate to lithium bis(trifluoromethanesulfonyl)imide is 1:(0.5-0.8); Preferably, the mass ratio of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide is 1:(0.3-1):(0.3-1); Preferably, the mass of the main component lithium salt is 10% to 20% of the total mass of the electrolyte; Preferably, the lithium salt further comprises a lithium salt additive, and the lithium salt additive comprises any one or a combination of at least two of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate or lithium tetrafluoroborate; Preferably, the mass of the lithium salt additive is 0.3% to 0.8% of the total mass of the electrolyte; Preferably, the organic solvent comprises a carbonate organic solvent and / or a carboxylate organic solvent; Preferably, the carbonate organic solvent includes a cyclic carbonate organic solvent and / or a linear carbonate organic solvent; Preferably, the organic solvent further comprises a diluent, and the diluent comprises ethylene glycol diacetate and / or tetrahydrofuran; Preferably, the mass of the organic solvent is 65% to 85% of the total mass of the electrolyte.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery electrolyte according to any one of claims 1 to 9.
Citation Information
Cited By
Cleaning composition as well as preparation method and application thereof
CN121320031A